PEMBUATAN POC ECOENZYM BERBASIS FERMENTASI TEPUNG DAUN KELOR YANG BERNUTRISI TINGGI DAN RAMAH LINGKUNGAN - Musadia Afa; Mustafa Mustafa; Hasbiadi Hasbiadi; La Mpia; La Ode Muhsafaat (Program Studi Agribisnis Fakultas Pertanian, 2023)
The current condition of Indonesian agriculture is very worrying due to the massive use of chemical fertilizers. One of the government's efforts to reduce the use of chemical fertilizers is to promote organic farming. Organic farming is the main indicator of realizing sustainable agriculture. One effort to develop organic farming is the use of liquid organic fertilizer (POC) based on fermented Moringa leaf flour which is highly nutritious and environmentally friendly. The procedure for making POC includes preparing materials and tools, making Moringa leaf flour and making POC by following predetermined procedures. The results of the research are making POC Ecoenzym through five core stages, namely preparation of tools and materials, grinding organic materials, mixing organic materials, brown sugar molasses and water, anaerobic fermentation process and filtering the POC Ecoenzym solution (results collection).